'Globesity' – aspects of obstetric care and pregnancy outcome in morbidly obese patients. (18th April 2012) - Edoo, AWI; Imcha, M; Hill, N; Cotter, A; Burke, G; Saunders, J; Fahy, U
Abstract : Objective: Maternal obesity is an important risk factor in modern obstetrics worldwide and its prevalence is rising. The aim of this retrospective review is to assess care and outcome in the morbidly obese pregnant patients. Methods: Hospital notes of every woman with a BMI ≥ 40 kg/m2 at their booking visit between January 2008 and December 2010 were studied retrospectively. Results: The incidence of morbid obesity among 11909 patients was 1.1% of whom 96.3%(126/131) were Caucasian. The median age was 30 years with a median BMI of 42 kg m2. The majority(64.2%) were multiparous with a previous caesarean section rate of 37%. On average morbidly obese patients had 4 scans during the pregnancy. 91.6%(120/131) had GTT and 16%(20/120) had gestational diabetes. 14.6% suffered from hypertension and 1.5% had IUGR. Ultrasound accurately estimated fetal weight in 64.4% of cases with a 10% margin of error. The caesarean section rate was 41.2% and instrumental delivery rate of 9.9%. The epidural analgesia uptake was 34% with an average insertion time of 20 minutes. 19.8% of patients had an anaesthetic review antenatally. The mean birth weight was 3.6kg (SD 600g) with no statistically significant difference(p=0.597) between diabetics and nondiabetics. There were 2 (2.5%) cases of shoulder dystocia and 1(1.3%) third degree tears among the 77 women who delivered vaginally. Conclusions: Ultrasound assessment of EFW seems to have similar accuracy in morbidly obese patients. Consideration should be given to developing specialised antenatal services as 60% of morbidly obese pregnant women require an operative delivery, with potentially difficult anaesthesia.